(untitled) - Meschede, Dieter (Weinheim, 2004)
The book introduces in detail the phenomena of linear and nonlinear light matter interaction, the properties of modern laser sources, and the concepts of quantum optics. Several examples taken from the scope of modern research are provided to emphasize the relevance of optics in current developments within science and technology
Keywords: Optics,Lasers,Photonics,Quang học,Kỹ thuật Lasers,Quang điện tử